Earnings Differentials and Returns to Education in China, 1995-2008 - Yuling Cui; Daehoon Nahm; Massimiliano Tani (Institute for the Study of Labor (IZA), 2013)
This paper estimates the returns to education of rural-urban migrants during the period of transition of China's economy between 1995 and 2008. Using data from CHIP and RUMiC, we find that rural migrants' earning differentials with urban residents are substantial and mainly depend on the type of occupation, industry, and employers' ownership, rather than the level of education completed. Returns to formal schooling for migrants remained stable at approximately 3% and 5% throughout the period, and differences across quantiles are generally statistically insignificant. Increasing gaps in the return to schooling by gender have instead emerged. These results raise questions about the incentives to invest in human capital for rural migrants and for the governments funding education in emigration regions.
Keywords: C31; J24; J61; O15; 330; returns to education; rural migrants; quantile regression; ownership enterprises; China; returns to schooling